The Pain Course: exploring the feasibility of an internet-delivered pain management programme for adults with spinal cord injury. Issue 10 (October 2018) - Dear, B.; Nicholson Perry, K.; Siddall, P.; Middleton, J.; Johnson, J.; Katte, L.; Monypenny, F.; Karin, E.; Gandy, M.; Titov, N.
Abstract Study design Single-group feasibility clinical trial. Objectives This study examined the feasibility and outcomes of a modified version of a validated internet-delivered pain management programme, the Pain Course, for adults with SCI. Setting Nationwide in Australia. Methods Sixty-eight adults participated in the programme, which comprises five online lessons and homework tasks that are systematically released over 8 weeks. Participants were supported through the course with weekly contact from a clinical psychologist. Results Eighty-five percent of participants provided data at post-treatment and 76% of participants completed all five lessons of the course. High levels of satisfaction were observed and relatively little clinician time (M = 93.16 min; SD = 52.76 min) was required per participant to provide the course. Preliminary evidence of clinical improvements in pain-related disability (ds ≥ 0.53.; avg. improvement ≥ 20%; Mdiff ≥ 7.77), depression (ds ≥ 0.44.; avg. improvement ≥ 24%; Mdiff ≥ 2.44), anxiety (ds ≥ 0.41.; avg. improvement ≥ 26%; Mdiff ≥ 1.8) and average pain intensity (ds ≥ 0.46.; avg. improvement ≥ 13%; Mdiff ≥ 0.71) were observed at post-treatment, which were maintained or further improved to 3-month follow-up. These improvements were reflected in overall improvements in self-reported satisfaction with life (ds ≥ 0.31; avg. improvement ≥ 25%; Mdiff ≥ 2.16) Conclusion These findings highlight the potential of carefully developed internet-delivered interventions as an approach for overcoming barriers and increasing access to psychosocial care for adults with SCI. Sponsorship iCare Lifetime Care and Support Authority and the Australian National Health and Medical Research Council.